Resin composition, polyurethane adhesive and laminate

By using a resin composition of high content polyurethane resin and a polyisocyanate curing agent, the polyester polyol and hydroxyl structure is optimized, and the problems of poor wetting and floating in the hot melting packaging processing of polyurethane-based adhesives are solved, thus realizing the laminated body Excellent adhesion and heat resistance ensure the appearance and moldability of the finished product.

CN118829701BActive Publication Date: 2024-12-27DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380025945.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-09-12
Filing Date
2023-03-13
Publication Date
2024-12-27
Estimated Expiration
2043-03-13

AI Technical Summary

Technical Problem

In the hot-supported packaging processing, existing polyurethane-based adhesives are prone to poor wetting, bubble mixing, floating, peeling and other defects, which affect the appearance and moldability of the finished product of the laminated body.

Method used

Using a resin composition containing more than 80% of polyurethane resin, the polyester polyol has a high content and a specific hydroxyl group and a diol structure, and combined with polyisocyanate as a curing agent, an adhesive layer with excellent adhesion and heat resistance is formed. , by adjusting the stoichiometric ratio of hydroxyl and isocyanate groups, the fluidity and wettability of the adhesive are optimized.

Benefits of technology

It is possible to achieve a situation where floating and peeling are not easily caused during molding processing such as drawing molding, ensuring a good appearance of the laminated body and excellent wetting properties to resins and metal substrates, and improving the moldability and heat resistance of the finished product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005030995930000141
    Figure GDA0005030995930000141
  • Figure GDA0005030995930000151
    Figure GDA0005030995930000151
  • Figure GDA0005030995930000201
    Figure GDA0005030995930000201
Patent Text Reader

Abstract

Provided is a resin composition useful as a main agent of a polyurethane adhesive that is excellent in wettability to substrates such as resins and metals and that can form an adhesive layer having excellent adhesiveness and heat resistance, and can produce a laminate that is not prone to defects such as floating and peeling even through molding such as drawing molding, and is excellent in wettability to substrates such as resins and metals. A resin composition is a resin composition for a polyurethane adhesive that is used together with a curing agent as a main agent of an adhesive. The resin composition contains a polyol (A), the polyol (A) contains 80% by mass or more of a polyurethane resin (c), the polyurethane resin (c) contains a structural unit derived from a polyol containing a polyester polyol (a), the polyester polyol (a) has a structural unit derived from a dicarboxylic acid component containing phthalic acid, the polyester polyol (a) has a terminal hydroxyl content of 0.1 to 2 mol / kg, and the polyurethane resin (c) has a terminal hydroxyl content of 0.04 to 0.4 mol / kg.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition used together with a curing agent as a main agent of a polyurethane adhesive, a polyurethane adhesive and a laminate. Background Art

[0002] As for the use of laminated bodies such as flexible packaging materials, for example, there are uses such as deep drawing to form a molded body such as packaging materials, filling the inside with contents, and then performing heat-welding and sealing processing (for example, food packaging for ham, pickled meat, etc.). During the heat-welding and sealing process, a high-temperature hot plate contacts the laminated body, but at this time, so-called "floating" sometimes occurs, where bubbles are mixed between layers at the location where heat and stress are concentrated. Moreover, when such "floating" occurs conspicuously, there are restrictions on the molding depth (filling volume of the contents), etc.

[0003] One of the raw materials of polyurethane used as the main agent of polyurethane adhesive is polyester polyol. Usually, polyurethane with polyester polyol having more phthalic acid content as raw material can be formed into an adhesive with improved heat resistance and adhesion to metals, etc. However, the more phthalic acid content of polyester polyol, the higher the viscosity of polyurethane and the lower the fluidity. Therefore, when using such adhesive with polyurethane as main agent to manufacture laminated body, it becomes easy to mix with bubbles caused by poor wetting, and it becomes easy to float in the obtained laminated body.

[0004] For example, an adhesive whose adhesion to substrates such as metals and resin films is instantaneously generated by irradiation with active energy rays has been proposed (Patent Document 1). In addition, a molding packaging material having NY / AL / PP layers and an adhesive used therein have been proposed (Patent Document 2). It should be noted that a technology for reducing the viscosity of polyester polyols having a high phthalic acid content and polyurethanes using the same has also been proposed (Patent Documents 3 and 4), but this has no effect on the moldability of the laminate. Furthermore, an adhesive composition containing a polyester urethane compound having a specific amount of trifunctional or higher hydroxyl groups has been proposed (Patent Document 5).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2015-13935

[0008] Patent Document 2: Japanese Patent Application Publication No. 2015-24862

[0009] Patent Document 3: Japanese Patent Application Publication No. 2007-8999

[0010] Patent Document 4: Japanese Patent Application Publication No. 2008-45101

[0011] Patent Document 5: Japanese Patent Application Publication No. 2017-25287 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] The floating caused by the mixing of bubbles due to poor wetting is a defect that detracts from the aesthetic value of the laminate. In addition, even small bubbles that are not noticeable may be stretched and enlarged during drawing. Furthermore, small bubbles expand due to the heat during the heat-welding packaging process (so-called heat-sealing process), making it easier to cause more noticeable floating and peeling. Therefore, even small bubbles cannot be ignored.

[0014] It can be said that the fluidity and wettability of the adhesive proposed in Patent Document 1 to the substrate are not good. Among them, in the roll-to-roll processing conditions that take productivity into consideration, the hot pressing becomes instantaneous, so it is sometimes easy to produce poor air bubble mixing due to insufficient wettability. In addition, the temperature during the aging of the adhesive proposed in Patent Document 2 is relatively high, and in flexible packaging materials, poor wetting is likely to occur under the usual aging conditions of about 40°C. Therefore, it is easy to produce poor air bubble mixing, and when aging is performed at high temperatures, it is disadvantageous in terms of energy cost. Furthermore, if the laminate obtained using the adhesive composition proposed in Patent Document 5 is subjected to drawing molding, undesirable conditions such as floating and peeling may sometimes occur, and there is room for improvement in the finished appearance of the product.

[0015] The present invention has been made in view of the problems of the prior art, and its object is to provide a resin composition that can form an adhesive layer with excellent adhesion and heat resistance, can produce a laminated body with good appearance that is not prone to defects such as floating and peeling even through molding processing such as drawing molding, and is useful as a main agent of a polyurethane-based adhesive with excellent wettability to substrates such as resins and metals.

[0016] Another object of the present invention is to provide a polyurethane adhesive having excellent wettability for substrates such as resins and metals, which can form an adhesive layer having excellent adhesiveness and heat resistance, and can produce a laminate having a good appearance and which is not prone to defects such as floating and peeling even through molding processes such as drawing molding.

[0017] Furthermore, an object of the present invention is to provide a laminate having an adhesive layer excellent in adhesiveness and heat resistance, which is less likely to cause defects such as floating and peeling even by a forming process such as drawing and has a good appearance.

[0018] Solutions for solving problems

[0019] That is, according to the present invention, there is provided the following resin composition.

[0020] [1] A resin composition for a polyurethane adhesive used together with a curing agent as a main agent of an adhesive,

[0021] The resin composition contains a polyol (A), wherein the polyol (A) contains 80% by mass or more of a polyurethane resin (c), wherein the polyurethane resin (c) has a structural unit derived from a polyol including a polyester polyol (a) and a structural unit derived from a polyisocyanate (b), and has a hydroxyl group at a molecular terminal thereof,

[0022] The polyester polyol (a) has a structural unit derived from a dicarboxylic acid component and a structural unit derived from a diol component.

[0023] The total content of phthalic acid and isophthalic acid in the dicarboxylic acid component is 50 mol% or more,

[0024] The content of the phthalic acid in the dicarboxylic acid component is 40 mol % or more,

[0025] The content of hydroxyl groups present at the molecular terminals of the polyester polyol (a) is 0.1 to 2 mol / kg,

[0026] In the polyol, the content of the polyester polyol (a) is 80% by mass or more,

[0027] The content of the hydroxyl group present at the molecular terminal of the polyurethane resin (c) is 0.04 to 0.4 mol / kg.

[0028] [2] The resin composition according to [1] above, wherein the content of hydroxyl groups present at the molecular terminals of the polyurethane resin (c) is 0.05 to 0.4 mol / kg.

[0029] [3] The resin composition according to [1] or [2], wherein the content of the phthalic acid other than the phthalic acid in the dicarboxylic acid component is 20 mol% or more.

[0030] [4] The resin composition according to any one of [1] to [3], wherein

[0031] The diol component includes a diol having two or three alkylene groups having 8 or less carbon atoms bonded via ether bonds in its molecule,

[0032] In the diol component, the content of the diol is 50 mol% or more.

[0033] [5] The resin composition according to any one of [1] to [4], further comprising 2% by mass or more of at least one organic solvent selected from the group consisting of ethyl acetate, methyl acetate, methyl ethyl ketone and dimethyl carbonate.

[0034] Furthermore, according to the present invention, there is provided the polyurethane-based adhesive described below.

[0035] [6] A polyurethane adhesive comprising a main agent and a curing agent,

[0036] The main agent is the resin composition described in any one of [1] to [5],

[0037] The aforementioned curing agent is polyisocyanate (B),

[0038] The stoichiometric ratio (NCO group / OH group) of the terminal isocyanate group (NCO group) of the polyisocyanate (B) to the terminal hydroxyl group (OH group) of the polyol (A) is 2.0 to 50.0.

[0039] Furthermore, according to the present invention, there is provided a laminated body shown below.

[0040] [7] A laminate comprising: two or more adherend layers; and an adhesive layer provided between the adherend layers and formed of the polyurethane adhesive according to [6] above.

[0041] [8] The laminate according to [7] above, wherein the adherend layer includes a metal layer.

[0042] [9] The laminated body according to [7] or [8] above, which has a molded portion molded into a concave shape.

[0043]

[10] The laminate according to any one of [7] to [9] above, which has a sealed portion sealed by heat fusion.

[0044] Effects of the Invention

[0045] According to the present invention, there can be provided a resin composition which can form an adhesive layer having excellent adhesiveness and heat resistance, can produce a laminate having good appearance and is not prone to defects such as floating and peeling even by molding such as drawing molding, and is useful as a main agent of a polyurethane-based adhesive having excellent wettability for substrates such as resins and metals.

[0046] In addition, according to the present invention, it is possible to provide a polyurethane adhesive having excellent wettability for substrates such as resins and metals, which can form an adhesive layer having excellent adhesiveness and heat resistance, and can produce a laminated body having a good appearance and which is not prone to defects such as floating and peeling even by molding such as drawing molding.

[0047] Furthermore, according to the present invention, it is possible to provide a laminate having an adhesive layer having excellent adhesiveness and heat resistance, which is less likely to cause defects such as floating and peeling even by a molding process such as drawing molding and has a good appearance. DETAILED DESCRIPTION

[0048] <Resin composition>

[0049] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following embodiments. One embodiment of the resin composition of the present invention is a resin composition for a polyurethane adhesive used together with a curing agent as a main agent of an adhesive. The resin composition of the present embodiment contains a polyol (A), and the polyol (A) contains more than 80% by mass of a polyurethane resin (c), and the polyurethane resin (c) has a structural unit derived from a polyol containing a polyester polyol (a) and a structural unit derived from a polyisocyanate (b), and has a hydroxyl group at its molecular end. Hereinafter, the details of the resin composition of the present embodiment will be described.

[0050] (Polyol (A))

[0051] The polyol (A) contains 80% by mass or more, preferably 90% by mass or more, of a polyurethane resin (c) having a hydroxyl group at a molecular terminal thereof. It should be noted that the polyol (A) is particularly preferably substantially composed of the polyurethane resin (c). If the content of the polyurethane resin (c) in the polyol (A) is less than 80% by mass, the adhesion of the obtained adhesive to a substrate such as a metal is reduced.

[0052] [Polyurethane resin (c)]

[0053] The polyurethane resin (c) has a structural unit derived from a polyol containing a polyester polyol (a) and a structural unit derived from a polyisocyanate (b). The polyester polyol (a) has a structural unit derived from a dicarboxylic acid component and a structural unit derived from a diol component. Moreover, in the dicarboxylic acid component, the total content of phthalic acid and isophthalic acid is 50 mol% or more, preferably 60 mol% or more, and more preferably 80 mol% or more. In the dicarboxylic acid component, if the total content of phthalic acid and isophthalic acid is less than 50 mol%, the adhesion of the obtained adhesive to a substrate such as a metal is reduced.

[0054] The content of phthalic acid in the dicarboxylic acid component is 40 mol% or more, preferably 60 mol% or more, and more preferably 80 mol% or more. If the content of phthalic acid in the dicarboxylic acid component is less than 40 mol%, the wettability of the obtained adhesive to the substrate is reduced.

[0055] As phthalic acid, phthalic acid and phthalic anhydride can be mentioned. It should be noted that alkyl esters of phthalic acid can also be used as phthalic acid. As isophthalic acid, isophthalic acid can be mentioned. It should be noted that alkyl esters of isophthalic acid can also be used as isophthalic acid.

[0056] The dicarboxylic acid component may further include acid components other than phthalic acid and isophthalic acid (other acid components). It should be noted that, in the dicarboxylic acid component, when the content of phthalic acid other than phthalic acid is 20 mol% or more, from the viewpoint of compensating for the decrease in wettability, the diol component of the polyester polyol (a) preferably includes a diol having 2 or 3 alkylene groups with a carbon number of 8 or less bonded by ether bonds in its molecule. Furthermore, the content of the diol in the diol component is preferably 50 mol% or more.

[0057] As other acid components, conventionally known monocarboxylic acids and polycarboxylic acids can be used, among which dicarboxylic acids having two carboxylic acid groups in one molecule are preferred.

[0058] As dicarboxylic acids, naphthalene dicarboxylic acid, adipic acid, azelaic acid, sebacic acid, succinic acid, glutaric acid, maleic acid, itaconic acid, their anhydrides, and alkyl esters can be mentioned. Among them, adipic acid is preferred. It should be noted that hydroxycarboxylic acids can also be treated in the same way as carboxylic acids according to the sum of their functional groups. That is, compounds having one carboxylic acid group and one hydroxyl group in one molecule can be used in the same way as dicarboxylic acids. As such compounds, glycolic acid, lactic acid, γ-hydroxybutyric acid, ε-hydroxycaproic acid, salicylic acid, and p-hydroxybenzoic acid can be mentioned. In addition, esters and lactones formed by dehydration of hydroxycarboxylic acids can also be used in the same way.

[0059] In the dicarboxylic acid component, the content of other acid components is preferably 50 mol% or less, more preferably 40 mol% or less, based on the entire dicarboxylic acid component.

[0060] The content of hydroxyl groups present at the molecular terminals of the polyester polyol (a) (hereinafter also referred to as "terminal hydroxyl group concentration" or "terminal OH group concentration") is 0.1 to 2 mol / kg, preferably 0.2 to 1.5 mol / kg, and more preferably 0.27 to 1.2 mol / kg. If the terminal OH group concentration of the polyester polyol (a) is less than 0.1 mol / kg, the wettability of the obtained adhesive to the substrate is reduced. On the other hand, if the terminal OH group concentration of the polyester polyol (a) exceeds 2 mol / kg, the formability of the laminate produced using the obtained adhesive is reduced.

[0061] The polyurethane resin (c) has a structural unit derived from a polyol and a structural unit derived from a polyisocyanate (b). The content of the polyester polyol (a) in the polyol is 80% by mass or more, preferably 90% by mass or more, and particularly preferably 100% by mass. That is, it is particularly preferred that the polyol constituting the polyurethane resin (c) is substantially formed only by the polyester polyol (a).

[0062] There is a hydroxyl group (OH group) at the molecular terminal of the polyurethane resin (c). The content of the hydroxyl group present at the molecular terminal of the polyurethane resin (c) (terminal hydroxyl group (OH group) concentration) is 0.04 to 0.4 mol / kg, preferably 0.05 to 0.3 mol / kg, and more preferably 0.06 to 0.25 mol / kg. If the terminal OH group concentration of the polyurethane resin (c) is less than 0.04 mol / kg, the wettability of the obtained adhesive to the substrate is reduced. On the other hand, if the terminal OH group concentration of the polyurethane resin (c) exceeds 0.4 mol / kg, the formability of the laminate manufactured using the obtained adhesive is reduced.

[0063] The polyurethane resin (c) has a structural unit derived from the polyisocyanate (b). As the polyisocyanate (b), a conventionally known polyisocyanate constituting a common polyurethane can be used. As the polyisocyanate, a diisocyanate having two isocyanate groups in the molecule and a molecular weight of 500 or less is preferred. As such a diisocyanate, for example, aromatic diisocyanates such as toluene diisocyanate and diphenylmethane diisocyanate; aliphatic diisocyanates such as hexamethylene diisocyanate, pentamethylene diisocyanate, isophorone diisocyanate, and lysine diisocyanate; etc. can be cited.

[0064] The polyester polyol (a) has a structural unit derived from a diol component. The diol component preferably contains a diol having two or three alkylene groups with a carbon number of 8 or less bonded via an ether bond in its molecule. By using such a diol having a specific structure, the wettability of the obtained adhesive to a substrate such as a resin or a metal can be further improved.

[0065] If the carbon number of the alkylene group of the diol is too large, the ratio of the structural unit derived from the dicarboxylic acid component in the polyester polyol (a) becomes relatively low. Therefore, the carbon number of the alkylene group of the diol is 8 or less, preferably 3 or less, and more preferably 2.

[0066] The number of ether bonds in the diol molecule is 2 or less, particularly preferably 1. If the number of ether bonds is 3 or more, the ratio of the structural unit derived from the dicarboxylic acid component in the polyester polyol (a) is relatively reduced, and the heat resistance of the obtained adhesive and the adhesion to substrates such as metals and polyester resins are likely to decrease.

[0067] Examples of the diol include diethylene glycol, triethylene glycol, and dipropylene glycol, and glycols obtained by ring-opening addition of ethylene, propylene, tetrahydrofuran, etc. to an alkylene glycol having a carbon number of 8 or less. Among them, diethylene glycol is preferred.

[0068] In the diol component, the content of the diol having a specific structure is preferably 50 mol% or more, more preferably 60 mol% or more, and more preferably 80 mol% or more. In the diol component, by making the content of the diol having a specific structure 50 mol% or more, the wettability of the obtained adhesive to substrates such as resins and metals can be further improved.

[0069] The diol component may further include an alcohol component other than the above diol having a specific structure. As the alcohol component that may be further included, a monohydric alcohol component or a polyhydric alcohol component known in the past may be used. Among them, a diol (other diols, diols) having two hydroxyl groups is preferred.

[0070] The polyester polyol (a) can be produced according to a conventionally known method for producing polyester resins. For example, a dicarboxylic acid component and a diol component are subjected to a polycondensation reaction at 140 to 250° C. in the presence of an esterification catalyst and an antioxidant as required, thereby obtaining the polyester polyol (a). As the esterification catalyst, an alkoxytitanium catalyst is preferably used. As the antioxidant, a phosphite compound is preferably used.

[0071] Polyurethane resin (c) can be manufactured according to the conventionally known method for manufacturing polyurethane and polyurethane urea. For example, polyester polyol (a) and polyisocyanate (b) are subjected to addition polymerization reaction together with other polyols, polyamine compounds and other active hydrogen compounds used as required at room temperature to 250°C, thereby obtaining polyurethane resin (c). The above-mentioned addition polymerization reaction can be carried out in the presence of a carbamate catalyst and an organic solvent as required. As a carbamate catalyst, a catalyst of a metal salt system such as tin, zinc, iron, bismuth, etc. is preferably used. During the above-mentioned addition polymerization reaction, the ratio of the amount (mole) of NCO groups to the amount (mole) of active hydrogen groups such as hydroxyl groups and amino groups (NCO groups / active hydrogen groups) is preferably set to 0.1 or more, and more preferably set to 0.4 or more.

[0072] (Organic Solvent)

[0073] The resin composition of the present embodiment preferably also contains an organic solvent. By also containing an organic solvent, the operability (stirring property during the synthesis of polyurethane resin, ease of taking out from the container, etc.) of the resin composition can be made good. As an organic solvent, it is preferred to use an organic solvent whose boiling point is 50 to 100° C., and from the viewpoints of operability, processability and low residual properties, organic solvents such as ethyl acetate, methyl acetate, methyl ethyl ketone and dimethyl carbonate are preferred. The content of the organic solvent in the resin composition is preferably more than 2% by mass, and more preferably 10 to 70% by mass.

[0074] (additive)

[0075] The resin composition of the present embodiment may further contain various additives. As additives, pigments, colorants, fillers, antibacterial agents, dispersants, stabilizers, ultraviolet absorbers, coupling agents, viscosity regulators, anti-blocking agents, defoamers, leveling agents, crosslinking agents, curing agents and fragrances may be cited.

[0076] <Polyurethane adhesive>

[0077] One embodiment of the adhesive of the present invention is a polyurethane adhesive containing a main agent and a curing agent, wherein the main agent is the aforementioned resin composition and the curing agent is a polyisocyanate (B). The following describes the details of the polyurethane adhesive of this embodiment (hereinafter also referred to as "adhesive").

[0078] (Polyisocyanate (B))

[0079] Polyisocyanate (B) is a component that functions as a curing agent of a polyurethane adhesive, and is used together with the aforementioned resin composition as a main agent. When the polyol (A) with a hydroxyl group is mixed with the polyisocyanate (B) with an isocyanate group that reacts chemically with the hydroxyl group, it becomes easy to produce phenomena such as viscosity rise and gelation over time, and the coating of the bonded layer sometimes becomes slightly difficult. Therefore, the adhesive of the present embodiment is preferably stored and transported in the form of the state before the mixed resin composition and the polyisocyanate (B), i.e., 2 components (two components). Then, the timing of mixing polyisocyanate (B) in the resin composition is preferably before the adhesive is about to be applied to the bonded layer (base material).

[0080] The stoichiometric ratio (NCO group / OH group) of the terminal isocyanate group (NCO group) of the polyisocyanate (B) of the adhesive of the present embodiment to the terminal hydroxyl group (OH group) of the polyol (A) in the resin composition is 2.0 to 50.0, preferably 5.0 to 25.0, and more preferably 7.0 to 20.0.

[0081] As the polyisocyanate (B), conventionally known polyisocyanate compounds can be used. Specifically, conventionally known polyisocyanates, adducts of polyisocyanates, cyanurates of polyisocyanates, biuret forms of polyisocyanates, polymers, and terminal isocyanate-type prepolymers can be cited as polyurethane raw materials and curing agents.

[0082] (Organic Solvent)

[0083] The adhesive of the present embodiment preferably further contains an organic solvent. By further containing an organic solvent, the coating property of a film-like or sheet-like substrate on the adhered layer can be improved. As the organic solvent, the same substances as the aforementioned organic solvents that can be contained in the resin composition can be cited.

[0084] (additive)

[0085] The adhesive of the present embodiment may further contain various additives. Examples of the additives include the same additives as those mentioned above that can be contained in the resin composition.

[0086] (Application of adhesive)

[0087] The adhesive of this embodiment is suitable as a material for bonding various substrates (adhesive layers) such as various plastic films, metal foils, metal vapor-deposited films, and transparent vapor-deposited films. The adhesive of this embodiment is suitable as a material for manufacturing a laminated body in which these various substrates are stacked and bonded to each other.

[0088] <Laminated body>

[0089] One embodiment of the laminate of the present invention comprises: two or more adherend layers; and an adhesive layer provided between the adherend layers and formed of the polyurethane adhesive. The laminate of this embodiment will be described in detail below.

[0090] (Adhesion layer)

[0091] As the substrate to be bonded, there can be cited resin films, sheets and foams; films coated with various polymer coating agents such as polyvinylidene chloride on the surface of resin films, etc.; films and sheets formed with inorganic layers such as metal vapor deposition, silica vapor deposition, and alumina vapor deposition; metal layers such as aluminum foil and copper foil; and woven fabrics, non-woven fabrics and paper, etc. As the resin constituting the resin film, in addition to polyolefins such as polyethylene and polypropylene, there can also be cited polystyrene, polyvinyl chloride, polyvinyl alcohol, their ethylene copolymers, polyamides such as nylon 6, polyesters such as polyethylene terephthalate (PET), etc. Surface treatment can be applied to these substrates. The Young's modulus (longitudinal elastic modulus) of the bonded layer at 120°C is preferably 0.05GPa or more. The Young's modulus (longitudinal elastic modulus) of conventional vinyl chloride (soft PVC, hard PVC) at 120°C is shown below.

[0092] Soft PVC (transparent): 0.01GPa

[0093] Soft PVC (with filling material): 0.045GPa

[0094] Rigid PVC (transparent): 0.029GPa

[0095] When the base material serving as the adhered layer is a metal layer and the metal layer is disposed in a portion accompanied by molding, the thickness of the metal layer is preferably 15 μm or more, more preferably 25 μm or more.

[0096] (Manufacturing of Laminated Body)

[0097] The laminate of the present embodiment can be manufactured according to the conventionally known method except using the aforementioned adhesive. First, polyisocyanate (B), organic solvent, etc. are added to the resin composition to prepare the adhesive for coating. After the obtained adhesive is applied to the surface of the bonded layer (the first substrate), a drying device such as a hot air heating type is used to remove the organic solvent and dry it. Then, after other bonded layers (the second substrate) are laminated, they are ripened under specified conditions, thereby obtaining the target laminate.

[0098] Usually, a dry laminator device is used to continuously apply, dry, laminate and reel the adhesive while unwinding the first and second substrates in a roll. As the method for applying the adhesive, for example, a gravure roller coating method, a reverse gravure roller coating method, an offset gravure roller coating method, and a reverse roller coating method can be cited.

[0099] Aging is a process of curing the applied adhesive to exhibit the required properties such as adhesion and heat resistance by maintaining the adhesive under appropriate temperature conditions for a specified time. The higher the aging temperature, the better the wettability of the adhesive to the substrate, and the better the curing reaction rate of the adhesive, so the time can be shortened. However, if the aging temperature is too high, the energy consumption increases, and the quality sometimes becomes easy to deteriorate depending on the type of substrate. Therefore, the aging temperature is preferably set to less than 60°C, and more preferably to 35-45°C.

[0100] In the case of laminating more than 3 layers of substrate, the above steps can be repeated. It should be noted that, regarding aging, multiple layers can be implemented in combination. In addition, adhesives with different compositions between each layer can be used, or adhesives with the same composition can be used. In the case of forming multiple adhesive layers, at least one adhesive layer can be formed by the polyurethane adhesive of this embodiment.

[0101] The laminate of the present embodiment can be used as a common soft packaging material, for example. In addition, the laminate of the present embodiment has excellent molding suitability, and the molded product (processed product) obtained by molding has excellent heat resistance. Therefore, it is suitable as a material constituting a packaging material (for example, a packaging material for food packaging purposes, etc.) having a molding processing portion formed into a concave shape, which is subjected to molding processing such as punching, bending, and drawing, and heat-welding and packaging processing on the laminate of the present embodiment.

[0102] The heat resistance of the molded body obtained by molding the stacked body can be evaluated based on the ease with which "floating" occurs when the parts where residual stress is concentrated (for example, the boundary between the bottom and the side when the nylon (NY) layer is on the inside and stretched into a concave shape, the boundary between the part where the nylon (NY) layer is on the outside and stretched into a concave shape and other parts such as the surrounding flange part) are exposed to high temperatures.

[0103] Example

[0104] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. It should be noted that "parts" and "%" in Examples and Comparative Examples are based on mass unless otherwise specified.

[0105] <Synthesis of polyester polyol (a)>

[0106] (Synthesis example 1)

[0107] Put 252.2 parts (8 mol) of phthalic anhydride, 62.2 parts (2 mol) of adipic acid, 112.7 parts (4 mol) of 1,6-hexanediol, 74.5 parts (3 mol) of neopentyl glycol and 44.4 parts (3 mol) of ethylene glycol in a flask. Heat at 230°C for 5 hours while stirring under a nitrogen stream, and carry out esterification reaction while letting water flow out. At the moment when the water flow stops, add 0.1 parts of titanium tetra-n-butoxide and 0.5 parts of triphenyl phosphite. While heating to 250°C, reduce the pressure to 10Torr for condensation reaction to obtain a polyester polyol (a1) with a terminal hydroxyl (OH group) concentration of 1.0 mol / kg. It should be noted that the terminal OH group concentration can be determined by quantitatively measuring the acetic acid that reacts with the hydroxyl group in the acetylation reaction based on acetic anhydride pyridine solution.

[0108] (Synthetic Examples 2 to 6, 9 to 18)

[0109] The formulations shown in Tables 1-1 and 1-2 were used, and except for this, polyester polyols (a2) to (a6) and (a11) to (a20) were obtained in the same manner as in the case of the polyester polyol (a1). The physical properties of the obtained polyester polyols are shown in Tables 1-1 and 1-2. It should be noted that the meanings of the abbreviations in Tables 1-1 and 1-2 are shown below.

[0110] tPA: terephthalic acid

[0111] iPA: Isophthalic acid

[0112] ·nPA: Phthalic anhydride

[0113] AA: Adipic acid

[0114] ·SA: Sebacic acid

[0115] 16HD: 1,6-Hexanediol

[0116] EG: Ethylene glycol

[0117] ·NPG: Neopentyl Glycol

[0118] ·DEG: Diethylene glycol

[0119] ·BoDC: Phthalic acid

[0120] ·BmDC: Isophthalic acid

[0121] ·BDC: benzene dicarboxylic acid

[0122] ·EDA: A diol having two or three alkylene groups having 8 or less carbon atoms bonded via ether bonds in its molecule

[0123] (Synthesis Example 7)

[0124] A mixture of polyester polyol (a4) and polyester polyol (a13) was obtained at a4 / a13 = 9 / 1 (mass ratio). The physical properties (average values) of the polyester polyol in the obtained mixture are shown in Table 1-1.

[0125] (Synthesis Example 8)

[0126] A mixture of a polyurethane resin (c4) and a polyurethane resin (c13) described below was mixed at c4 / c13=9 / 1 (mass ratio) was obtained. The physical properties (average values) of the polyester polyol in the obtained mixture are shown in Table 1-1.

[0127] Table 1-1

[0128] Table 1-2

[0129]

[0130] <Manufacturing of resin composition>

[0131] (Example 1)

[0132] 150 parts of polyester polyol (a1), 10.45 parts of toluene diisocyanate (TDI), 40.11 parts of methyl ethyl ketone (MEK) and 0.075 parts of zinc octylate were added to a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 120.34 parts of MEK were added to obtain a solution of a polyurethane resin (c1). 1.6 parts of a silane coupling agent (trade name "KBM-403", manufactured by Shin-Etsu Silicone Co., Ltd.) and 1.6 parts of MEK were added to the obtained solution of the polyurethane resin (c1) and uniformly mixed to obtain a resin composition (R-1).

[0133] (Example 2)

[0134] 150 parts of polyester polyol (a2), 3.48 parts of TDI, 38.37 parts of MEK and 0.075 parts of zinc octylate were added to a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 115.11 parts of MEK were added to obtain a solution of polyurethane resin (c2). 1.53 parts of silane coupling agent (KBM-403) and 1.53 parts of MEK were added to the obtained solution of polyurethane resin (c2) and uniformly mixed to obtain a resin composition (R-2).

[0135] (Example 3)

[0136] 150 parts of polyester polyol (a3), 6.97 parts of TDI, 39.24 parts of MEK and 0.075 parts of zinc octylate were added to a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 117.71 parts of MEK were added to obtain a solution of a polyurethane resin (c3). 1.57 parts of a silane coupling agent (KBM-403) and 1.57 parts of MEK were added to the obtained solution of the polyurethane resin (c3) and uniformly mixed to obtain a resin composition (R-3).

[0137] (Example 4)

[0138] 150 parts of polyester polyol (a4), 6.97 parts of TDI, 39.24 parts of MEK, and 0.075 parts of zinc octylate were placed in a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 117.7 parts of MEK were added to obtain a solution of a polyurethane resin (c4). 1.57 parts of a silane coupling agent (KBM-403) and 1.57 parts of MEK were added to the obtained solution of the polyurethane resin (c4) and uniformly mixed to obtain a resin composition (R-4).

[0139] (Example 5)

[0140] 150 parts of polyester polyol (a5), 6.67 parts of isophorone diisocyanate (IPDI), 39.16 parts of ethyl acetate (EA) and 0.075 parts of zinc octylate were placed in a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 117.50 parts of ethyl acetate (EA) were added to obtain a solution of a polyurethane resin (c5). 1.57 parts of a silane coupling agent (KBM-403) and 1.57 parts of EA were added to the obtained solution of the polyurethane resin (c5) and uniformly mixed to obtain a resin composition (R-5).

[0141] (Example 6)

[0142] 150 parts of polyester polyol (a6), 3.75 parts of diphenylmethane diisocyanate (MDI), 38.44 parts of methyl acetate (MA) and 0.075 parts of zinc octylate were placed in a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 116.85 parts of methyl acetate (MA) were added to obtain a solution of polyurethane resin (c6). 1.54 parts of silane coupling agent (KBM-403) and 1.54 parts of dimethyl carbonate (DMC) were added to the obtained solution of polyurethane resin (c6) and uniformly mixed to obtain a resin composition (R-6).

[0143] (Example 7)

[0144] 135 parts of polyester polyol (a4), 15 parts of polyester polyol (a13), 0.23 parts of 1,3-butanediol (13BD), 0.22 parts of trimethylolpropane (TMP), 5.11 parts of hexamethylene diisocyanate (HDI), 2.85 parts of toluene diisocyanate (TDI), 39.58 parts of EA and 0.075 parts of zinc octylate were placed in a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 120.32 parts of toluene (TOL) were added to obtain a solution of a polyurethane resin (c7). 1.57 parts of a silane coupling agent (KBM-403) and 1.57 parts of TOL were added to the obtained solution of the polyurethane resin (c7) and uniformly mixed to obtain a resin composition (R-7).

[0145] (Example 8)

[0146] 135 parts of the polyurethane resin (c4) solution and 15 parts of the polyurethane resin (c13) solution were uniformly mixed with 0.75 parts of a silane coupling agent (KBM-403) and 0.75 parts of MEK to obtain a resin composition (R-8).

[0147] (Example 9)

[0148] To 88 parts of the polyurethane resin (c4) solution, 5.28 parts of an epoxy resin (trade name "jER1004", manufactured by Mitsubishi Chemical Corporation), 0.49 parts of a silane coupling agent (KBM-403), and 5.77 parts of MEK were added and uniformly mixed to obtain a resin composition (R-9).

[0149] (Comparative Example 1)

[0150] 150 parts of polyester polyol (a11), 6.97 parts of TDI, 39.24 parts of MEK and 0.075 parts of zinc octylate were placed in a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 117.73 parts of MEK were added to obtain a solution of polyurethane resin (c11). 1.57 parts of silane coupling agent (KBM-403) and 1.57 parts of MEK were added to the obtained solution of polyurethane resin (c11) and uniformly mixed to obtain a resin composition (R-11).

[0151] (Comparative Example 2)

[0152] 150 parts of polyester polyol (a12), 4.18 parts of TDI, 38.55 parts of MEK and 0.075 parts of zinc octylate were added to a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 115.64 parts of MEK were added to obtain a solution of a polyurethane resin (c12). 1.54 parts of a silane coupling agent (KBM-403) and 1.54 parts of MEK were added to the obtained solution of the polyurethane resin (c12) and uniformly mixed to obtain a resin composition (R-12).

[0153] (Comparative Example 3)

[0154] 150 parts of polyester polyol (a13), 6.97 parts of TDI, 39.24 parts of MEK and 0.075 parts of zinc octylate were added to a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 117.73 parts of MEK were added to obtain a solution of a polyurethane resin (c13). 1.57 parts of a silane coupling agent (KBM-403) and 1.57 parts of MEK were added to the obtained solution of the polyurethane resin (c13) and uniformly mixed to obtain a resin composition (R-13).

[0155] (Comparative Example 4)

[0156] 150 parts of polyester polyol (a14), 6.97 parts of TDI, 39.24 parts of MEK and 0.075 parts of zinc octylate were placed in a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 117.73 parts of MEK were added to obtain a solution of a polyurethane resin (c14). 1.57 parts of a silane coupling agent (KBM-403) and 1.57 parts of MEK were added to the obtained solution of the polyurethane resin (c14) and uniformly mixed to obtain a resin composition (R-14).

[0157] (Comparative Example 5)

[0158] 150 parts of polyester polyol (a15), 23.23 parts of TDI, 43.31 parts of MEK, and 0.075 parts of zinc octylate were placed in a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 129.92 parts of MEK were added to obtain a solution of a polyurethane resin (c15). 1.73 parts of a silane coupling agent (KBM-403) and 1.73 parts of MEK were added to the obtained solution of the polyurethane resin (c15) and uniformly mixed to obtain a resin composition (R-15).

[0159] (Comparative Example 6)

[0160] 150 parts of polyester polyol (a16), 1.74 parts of TDI, 37.94 parts of MEK and 0.075 parts of zinc octylate were placed in a flask. After reacting at 80°C for 7 hours under a nitrogen stream, 113.81 parts of MEK were added to obtain a solution of a polyurethane resin (c16). 1.52 parts of a silane coupling agent (KBM-403) and 1.52 parts of MEK were added to the obtained solution of the polyurethane resin (c16) and uniformly mixed to obtain a resin composition (R-16).

[0161] (Comparative Example 7)

[0162] 150 parts of polyester polyol (a17), 6.97 parts of TDI, 39.24 parts of MEK, and 0.075 parts of zinc octylate were placed in a flask and reacted, but a uniform solution was not obtained and a solution of polyurethane resin (c17) could not be obtained.

[0163] (Comparative Example 8)

[0164] 0.5 parts of a silane coupling agent (KBM-403) and 50.5 parts of MEK were added to 50 parts of the polyester polyol (a18), and the mixture was uniformly mixed to obtain a resin composition (R-18).

[0165] (Comparative Example 9)

[0166] 1053 parts of polyester polyol (a18) and 73.4 parts of HDI were added to a flask. After reacting at 75°C for 8 hours under a nitrogen stream, 1126.4 parts of MEK were added to obtain a solution of a polyurethane resin (c18). 1.13 parts of a silane coupling agent (KBM-403) and 1.13 parts of MEK were added to the obtained solution of the polyurethane resin (c18) and the mixture was uniformly mixed to obtain a resin composition (R-19).

[0167] (Comparative Example 10)

[0168] 500 parts of the polyester polyol (a20) obtained in Synthesis Example 18, 56 parts of TDI and 257 parts of ethyl acetate (EA) were added to a flask. The mixture was reacted at 80°C for 5 hours under a nitrogen stream to obtain a terminal diisocyanate prepolymer with TDI added to both ends of the polyester polyol. 43.1 parts of trimethylolpropane (TMP) and 713 parts of EA were placed in another flask. After uniform dissolution, 741.3 parts of the terminal diisocyanate prepolymer was added while stirring. The mixture was stirred and reacted at 80°C for 5 hours under a nitrogen stream. 1 mol of TMP was completely added to each 1 mol of isocyanate group at both ends of the terminal diisocyanate prepolymer. As a result, a solution of a polyurethane resin (c19) having a trifunctional or higher hydroxyl group was obtained.

[0169] After adding 60 parts of ethyl acetate (EA) to 40 parts of polyester polyol (a19) and uniformly mixing, 25 parts of a solution of a polyurethane resin (c19) and 0.525 parts of a silane coupling agent (KBM-403) were further uniformly mixed to obtain a resin composition (R-20).

[0170] The details of the produced polyurethane resin (c) are shown in Tables 2-1 and 2-2. The details of the produced resin composition are shown in Tables 3-1 and 3-2.

[0171] Table 2

[0172]

[0173] Table 22

[0174]

[0175] Table 3-1

[0176]

[0177] Table 3-2

[0178]

[0179] <Manufacturing of adhesives>

[0180] (Examples 10 to 19, Comparative Examples 11 to 21)

[0181] The components shown in Tables 4-1 and 4-2 were mixed to obtain adhesives U1 to U21. The meanings of the abbreviations in Tables 4-1 and 4-2 are shown below.

[0182] · D-103: Isocyanate curing agent (trade name "TAKENATE D-103", manufactured by Mitsui Chemicals, Inc., polyisocyanate)

[0183] HL: isocyanate curing agent (trade name "CORONATE HL", manufactured by Tosoh Corporation, polyisocyanate)

[0184] · TPA-100: Isocyanate curing agent (trade name "DURANATE TPA-100", manufactured by Asahi Kasei Chemicals Corporation, polyisocyanate)

[0185] ·D-165N: Isocyanate curing agent (trade name "TAKENATE D-165N", manufactured by Mitsui Chemicals, Inc., polyisocyanate)

[0186] ·HX: isocyanate curing agent (trade name "CORONATE HX", manufactured by Tosoh Corporation, polyisocyanate)

[0187] ·D-165N / HX: A mixture of the above D-165N and HX in a mass ratio of 1:1

[0188] Table 4-1

[0189]

[0190] Table 4-2

[0191]

[0192] <Manufacturing of laminated body>

[0193] (Examples 20 to 29, Comparative Examples 22 to 32)

[0194] The adhesive was applied to one substrate using a bar coater #12 and then dried in a hot air drying oven at 80°C. Another substrate was placed on the dried adhesive and rolled. After that, the adhesive was aged at 40°C for 5 days to obtain laminates (L1) to (L21). The substrates used are shown below.

[0195] NY#15: Nylon film, trade name "EMBLEM ON", manufactured by UNITIKA LTD., thickness 15 μm, Young's modulus 0.45 GPa (120°C)

[0196] NY#25: Nylon film, trade name "EMBLEM ON", manufactured by UNITIKA LTD., thickness 25 μm, Young's modulus 0.45 GPa (120°C)

[0197] RCPP#60: Retort (heat-resistant) unstretched polypropylene film, trade name "PYLEN Film-CT P1146", manufactured by TOYOBO Co., Ltd., thickness 60 μm, Young's modulus 0.061 GPa (120°C)

[0198] AL#100: aluminum foil, trade name "Bare Foil A1N30", manufactured by UACJ Corporation, thickness 100 μm, Young's modulus 65 GPa (120°C)

[0199] <Evaluation>

[0200] (Thermal Packaging)

[0201] The RCPP layers of the laminate (NY#15 / RCPP#60) were brought into close contact with each other, and the NY layer was pressed and heat-sealed using a hot plate at 200°C for 1 second to produce a packaging material.

[0202] (Cooking test)

[0203] A cooking test was conducted in which mayonnaise was placed in the prepared packaging material, the packaging material was sealed, and the packaging material was heated at 120°C for 30 minutes.

[0204] (Appearance of laminated body)

[0205] The produced laminate was visually observed, and the appearance of the laminate was evaluated based on the following evaluation criteria. The results are shown in Tables 5-1 and 5-2.

[0206] ◎: Very good

[0207] ○: Good (transparency and brightness decreased slightly)

[0208] △: There is a small float

[0209] ×: There is large lifting and peeling

[0210] (Determination of peel strength / package strength)

[0211] A strip-shaped test piece with a width of 15 mm was cut out from the manufactured laminate. Using the cut test piece, T-peeling was performed at a speed of 300 mm / min between the chucks, and the peeling strength (N / 15 mm) was measured. Similarly, a strip-shaped test piece with a width of 15 mm was cut out from the thermal packaging portion, and the packaging strength (N / 15 mm) was measured. The results are shown in Tables 5-1 and 5-2. It should be noted that in Tables 5-1 and 5-2, "fa" indicates that peeling occurred at the interface between the NY layer and the adhesive layer, "aa" indicates that (aggregation) peeling occurred in the adhesive layer, and "am" indicates that peeling occurred at the interface between the adhesive layer and the metal layer (aluminum foil).

[0212] (Moldability)

[0213] A test piece with a diameter of 6 cm was cut out from the manufactured laminate (NY#25 / AL#100). A deep drawing tester equipped with a punch (diameter: 30 mm, shoulder r: 1 mm) was used to perform drawing forming with the NY layer side of the test piece as the inner side, and a molded body with a recess of 5 mm in depth was obtained. The obtained molded body was visually observed, and the moldability was evaluated according to the evaluation criteria shown below. The results are shown in Tables 5-1 and 5-2.

[0214] ○: Good

[0215] ×: There is floating or peeling

[0216] (Heat resistance after molding)

[0217] The molded body produced in the evaluation of "molding property" was placed in a thermostatic chamber set at 120°C, 160°C and 200°C for 1 hour each. The connection between the bottom surface and the side surface at the inner surface side of the concave portion of the molded body taken out from the thermostatic chamber was visually observed, and the heat resistance after molding was evaluated according to the evaluation criteria shown below. The results are shown in Tables 5-1 and 5-2.

[0218] ○: No floating occurs

[0219] △: Floating with a major diameter less than 0.5 mm occurred

[0220] ×: Floating or peeling with a major diameter of 0.5 mm or more occurred

[0221] Table 5-1

[0222]

[0223] Table 5-2

[0224]

[0225] Industrial Applicability

[0226] The resin composition of the present invention is useful as a material for producing a laminate constituting a packaging material for food packaging that is subjected to a draw molding process or a heat-welding sealing process, for example.

Claims

1. A resin composition for a polyurethane adhesive used as a main agent of an adhesive together with a curing agent, The resin composition contains a polyol (A), wherein the polyol (A) contains 80% by mass or more of a polyurethane resin (c), wherein the polyurethane resin (c) has a structural unit derived from a polyol including a polyester polyol (a) and a structural unit derived from a polyisocyanate (b), and has a hydroxyl group at a molecular terminal thereof, The polyester polyol (a) has a structural unit derived from a dicarboxylic acid component and a structural unit derived from a diol component. The total content of phthalic acid and isophthalic acid in the dicarboxylic acid component is 50 mol% or more, The content of the phthalic acid in the dicarboxylic acid component is 40 mol % or more, The content of hydroxyl groups present at the molecular terminals of the polyester polyol (a) is 0.1 to 2 mol / kg, In the polyol, the content of the polyester polyol (a) is 80% by mass or more, The content of the hydroxyl group present at the molecular terminal of the polyurethane resin (c) is 0.04 to 0.4 mol / kg.

2. The resin composition according to claim 1, wherein The content of the hydroxyl group present at the molecular terminal of the polyurethane resin (c) is 0.05 to 0.4 mol / kg.

3. The resin composition according to claim 1, wherein In the dicarboxylic acid component, the content of phthalic acid other than the phthalic acid is 20 mol% or more.

4. The resin composition according to claim 1, wherein The diol component includes a diol having two or three alkylene groups having 8 or less carbon atoms bonded via ether bonds in its molecule, In the diol component, the content of the diol is 50 mol% or more. 5 . The resin composition according to claim 1 , further comprising 2 mass % or more of at least one organic solvent selected from the group consisting of ethyl acetate, methyl acetate, methyl ethyl ketone and dimethyl carbonate.

6. A polyurethane adhesive comprising a main agent and a curing agent, The main agent is the resin composition according to any one of claims 1 to 5, The curing agent is polyisocyanate (B), The stoichiometric ratio (NCO group / OH group) of the terminal isocyanate group (NCO group) of the polyisocyanate (B) to the terminal hydroxyl group (OH group) of the polyol (A) is 2.0 to 50.

0. 7 . A laminate comprising: two or more adherend layers; and an adhesive layer provided between the adherend layers and formed of the polyurethane adhesive according to claim 6 .

8. The laminate according to claim 7, wherein: The bonded layer includes a metal layer. 9 . The laminated body according to claim 7 , comprising a molded portion molded into a concave shape. 10 . The laminated body according to claim 7 , comprising a sealing portion sealed by heat fusion.